Thermal electric generator prototype for marine engine - Nadarajoo, Sarveshvaran (2018)
The concept of Thermoelectric power generation where heat is converted to electrical energy, was first conceived in the 19th century. However due to its relatively low efficiency, it is not widely sourced. With the global increase in power consumption and depleting finite source of fossil fuels coupled with an increased awareness of climate change, renewable sources of energy is beginning to take importance. With recent technological advancements in the semiconductor and material engineering fields where new materials with larger figures of merit are being researched on. Thermoelectric power generations systems are becoming much more viable and attractive than it used to be. New materials alone, are not the only factors to increase the efficiency of Thermoelectric modules, multiple studies have been conducted to increase the efficiency of TEMs through various methods and designs. In this project, various TEMs were tested to ascertain their performance characteristics in varying temperature conditions and to improve the architecture of the test rig to optimise the efficiency of the modules. Experiments with a Phase change material were also conducted to better understand their effects on the overall power generation of the modules. The experiments were setup to closely reflect the conditions of implementing a TEG system in a marine diesel engine application. A detailed selection process is carried out to ascertain the suitable PCMs to be integrated with the system. The study also verifies the impact of adding conductive materials such as copper foam into the PCM container with respect to heat dissipation of the PCM. More investigations should be carried to draw conclusions on the effectiveness of integrating PCMs on both sides of the TEG in maritime applications.